The cardiotoxicity of antimalarials - Chan, X (World Health Organization, 2017)
The cardiotoxicity of antimalarial medicines has received renewed interest in recent years following the ‘Thorough QT’ assessment of the dihydroartemisinin-piperaquine formulation approved by the European Medicines Agency, which showed evidence of QT interval prolongation. Piperaquine is a bisquinoline antimalarial that is structurally related to chloroquine. Many drugs among the quinoline and structurally-related medicines affect myocardial depolarization and repolarization. WHO currently recommends the artemisinin-based combination treatment dihydroartemisinin-piperaquine for the treatment of uncomplicated malaria. This treatment is being considered alongside other antimalarial medicines for preventive therapy and mass drug administration. To inform WHO recommendations, a group of experts met in October 2016 to review evidence on the cardiotoxicity risk of quinoline antimalarials and structurally-related medicines in people with and without clinical malaria. The following recommendations were proposed by the WHO Evidence Review Group for consideration by the WHO Malaria Policy Advisory Committee and the WHO Advisory Committee on Safety of Medicinal Products.